Laminated Wood Material Reinforced with Bacterial Cellulose Sheets Derived from Kombucha Pellicles: Part 1 — Some Physical Properties - Mehmet Budakçı; Diğdem Şağban; Mustafa Korkmaz; Izham Kılınç (BioResources)
In this study, the usability of kombucha pellicles as a source of bacterial cellulose (BC) in the production of laminated wood was investigated to improve its physical properties. Within this scope, the kombucha culture was produced at room temperature through a fermentation process of approximately 25 days and then dried to obtain BC sheets with a thickness of approximately 1 mm. These sheets were used in the production of laminated wood material, along with wood species of Scots pine (Pinus sylvestris L.), Oriental beech (Fagus orientalis L.), and Anatolian chestnut (Castanea sativa Mill.), using urea-formaldehyde, polyurethane, and polyvinyl acetate adhesives. To evaluate the physical properties of the manufactured samples, density, thickness swelling, and water absorption tests were performed. Furthermore, the structural and thermal properties of the BC were analyzed using scanning electron microscopy and thermogravimetric analysis techniques. The findings indicated that BC is a high-performance biomaterial for lamination. The results unveiled BC's remarkable potential for developing eco-friendly materials, though certain technical challenges remain to be addressed before its full capabilities can be realized.